Reliability Evaluation of Improved Sampling Method for Mechanical Test of Cable Insulation - Seung-Won Lee; Jin-Wook Choe; Ik-Su Kwon; Jin-Seok Lim; Byung-Bae Park; Hae-Jong Kim (Energies)
Underground and submarine power cables are subjected to mechanical stress during installation and operation, which degrades the cable insulation and reduces the reliability of power transmission. Therefore, tests that can evaluate the mechanical properties of power cable insulation are very important. The purpose of this paper is to introduce an improved sampling method for the test sample, the peeling, for mechanical testing of power cable insulation and to evaluate the reliability of the method. The influence of the sampling method of the test sample on the mechanical property values was analyzed. The tensile strength and elongation of XLPE (cross-linked polyethylene) and PP (polypropylene) insulation prepared by the slice method and the peeling method were measured, and the surface of the test samples according to the sampling methods was photographed by SEM. The results show that the mechanical property of the cable insulation increased by more than 10% when the improved peeling method was used, and the precision of the peeling method was relatively better. The SEM analysis showed that the surface of the sliced test sample was rougher than the peeled test sample and was physically damaged. Therefore, the high reliability of the peeling method for mechanical testing of cable insulators was demonstrated.